History and Role of the Barmak Family in the Abbasid Dynasty Government in Baghdad (786-803 AD) - Ibnu Rusydi; Zaenullah (al-Afkar, Journal For Islamic Studies, 2024)
This paper aims to study and analyze the history and role of the Barmak family in the Abbasid Dynasty government in Baghdad (786-803). The method used in this research is historical research. The historical method here is the process of testing and analyzing critically records and relics of the past. This study concluded that the Barmak family was the first non -Arab person to have the highest authority in the government affairs of the Abbasid Dynasty. This family controlled the government affairs of the Abbasid Dynasty from 786 AD to 803 M.45, namely in the five periods of the Caliph Abbasid. Namely during the time al-Saffah, al-Mansur, al-Mahdi, al-Hadi, al-Rashid. The Barmak family occupied the honorable position during the Abbasid Caliph. The wheels of government and the Caliphate Bureau of the Abbasid Dynasty were carried out by the Vice -Agency (Minister). The family of the Barmak whose family head was Khālid was appointed as Wazir by Al-Mansur and his descendants of Yahya, Fadhl, and Ja'far Ibn Barmak held that position under the Caliphs. The Barmakiah family are all famous for smart and smart people. This family succeeded in making the Caliph Harun al-Rashid the best caliph in the Abbasid era and succeeded in bringing the kingdom to reach a golden age. The fate of this family ended tragically, since 187 H/803 AD the direction of Al-Rashid's policy changed by massacre to the Barmak people which resulted in imprisonment of Yahya and Al-Fadhl, and the execution of Jaʿfar Ibn Barmak.